2013
DOI: 10.1080/07924259.2013.797935
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine aspects of ovary growth and gestation in the Argentinian cockroach,Blaptica dubia(Dictyoptera, Blaberidae)

Abstract: Titers of juvenile hormone (JH) III and free ecdysteroids were studied in the hemolymph of the ovoviviparous Argentinian cockroach, Blaptica dubia, related to fat body depletion and reproduction. Adult females were analyzed during the first (days 5-25) and second vitellogenic cycle (days 80-100) and during the periods of gestation. Body weight changes of adult females were closely related to ovarian growth, ootheca formation, ootheca deposition, and hatching of the nymphs. Biochemical analysis of the fat body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Blaptica dubia is a quite large (up to 45 mm in length) sexually dimorphic blaberid cockroach (Wu, 2013). They typically live in aggregations at high temperature and humidity in central and south America (Alamer & Hoffmann, 2014), consuming vegetative matter, and are ovoviviparous. They are described as “gregarious” (Grandcolas, 1998) or “communal” as individuals of the same generation cohabit (without shared parental care; Bewick et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Blaptica dubia is a quite large (up to 45 mm in length) sexually dimorphic blaberid cockroach (Wu, 2013). They typically live in aggregations at high temperature and humidity in central and south America (Alamer & Hoffmann, 2014), consuming vegetative matter, and are ovoviviparous. They are described as “gregarious” (Grandcolas, 1998) or “communal” as individuals of the same generation cohabit (without shared parental care; Bewick et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that changes in the concentrations of JH III and free ecdysteroids in the haemolymph of B. dubia adult females are strongly related to the reproductive processes of ovarian growth, ootheca formation and egg deposition (Alamer and Hoffmann 2013). JH III seems to be the major gonadotropic hormone, but ecdysteroids may modulate vitellogenesis and egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Cockroaches, B. dubia, were maintained as described earlier (Alamer and Hoffmann 2013). Under our rearing conditions, first mating occurred at day 4 after adult emergence, ovulation was observed at day 19 ± 4 and oviposition started on day 69 ± 5 of adult life (n = 10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations